The Initial Impact of the Anatomical Society Gross Anatomy Core Syllabus for Medicine in the United Kingdom: Student and Teacher Perspectives. Issue 5 (8th November 2018) - Smith, Claire F.; Finn, Gabrielle M.; Hennessy, Catherine; Luscombe, Ciara; Stewart, Jane; McHanwell, Stephen
Abstract : "What do students studying medicine need to know" is an important question for curriculum planners, anatomy educators and students. The Core Regional Anatomy Syllabus (CRAS), published by the Anatomical Society in 2016, contains 156 learning outcomes (LOs) and has informed "what needs to be known." This project explored how CRAS had impacted undergraduate anatomy and anatomists in the United Kingdom. A cross‐sectional study was designed in two phases. Phase 1, involved a survey of students in clinical years (N = 164). Phase 2 included a survey of anatomist's views (n = 50) and focus groups of anatomy educators (N = 16). The students' perspective showed that specific regions of CRAS are deemed less relevant. These were also the body areas where students perceived their anatomical knowledge to be more deficient. Only 46% (n = 75) of students estimated that they knew over 50% (n = 78) of the LOs. Phase two revealed that all anatomists were aware of the syllabus and 48% (n = 24) had checked the CRAS against their own institutional LOs. Anatomists had shared CRAS with colleagues 64% (n = 32) and students at 34% (n = 17), respectively. Forty‐six percent (n = 23) of anatomists reported having changed their teaching in some way because of CRAS. The focus groups generated four key themes: "support for CRAS, " "standardization and validation, " "professional identity, " and "limitations and leverage." Overall CRAS has been well received and is establishing itself within the anatomical community as the new standard for anatomy teaching for medical students.